Dectin-1 stimulates IL-33 expression in dendritic cells via upregulation of IRF4. (June 2018) - Wang, Dongjiao; Gao, Sujun; Chen, Jintong; Zhao, Yinghua; Jiang, Yuxue; Chu, Xiao; Wang, Xiaohua; Liu, Ning; Qin, Tianxue; Yi, Qing; Yue, Ying; Wang, Siqing
Abstract Interleukin-33 (IL-33) is a potent contributor to antiviral immune responses and antitumor immunity. We recently discovered that IL-33 is overexpressed in dectin-1-activated dendritic cells (DCs). However, mechanisms of dectin-1-induced IL-33 expression in DCs remain elusive. Curdlan, an agonist of dectin-1, was used to mature DCs in this study. We found that dectin-1-induced IL-33 expression in DCs relies on Syk and Raf-1 pathways. By using nuclear factor (NF)-κB inhibitors, we also found that dectin-1-induced IL-33 expression relies on NF-κB signaling. Furthermore, through Syk/Raf-1-NF-κB pathway, dectin-1 signaling stimulates DCs to overexpress interferon regulatory factor 4 (IRF4), which directly upregulates the expression of IL-33 in dectin-1-activated DCs. Thus, our study provides new insights into the mechanisms of dectin-1-induced IL-33 expression in DCs and may provide new targets for improving DC-based cancer immunotherapy.